2009
DOI: 10.1080/09518390902835421
|View full text |Cite
|
Sign up to set email alerts
|

Laughter and forgetting: using focus groups to discuss smoking and motherhood in low‐income areas in the UK

Abstract: This article considers previously ignored aspects of verbal communication, humor and laughter, as critical components of social interaction within group discussions. Drawing on data from focus groups, Robinson uses a feminist perspective to explore how mothers living in areas of poverty in Liverpool, UK, use humor and laughter to discuss their experiences of smoking and caring for children. While laughter enabled some women to talk about sensitive and private issues, humor was also used by some women as a form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…In terms of the use of focus groups as a way to overcome a sense of discomfort in talking about the intimate aspects of practice, when asked if the topic of conversation made them feel uncomfortable the overwhelming majority disagreed (87.6% – with 56.3% disagree; 31.3% strongly disagree). This supports previous research that has shown that focus groups are a successful way of discussing sensitive topics (Robinson ; Wilkinson et al . ).…”
Section: Reflections On the Use Of Focus Groups And Humour To Capturesupporting
confidence: 91%
See 2 more Smart Citations
“…In terms of the use of focus groups as a way to overcome a sense of discomfort in talking about the intimate aspects of practice, when asked if the topic of conversation made them feel uncomfortable the overwhelming majority disagreed (87.6% – with 56.3% disagree; 31.3% strongly disagree). This supports previous research that has shown that focus groups are a successful way of discussing sensitive topics (Robinson ; Wilkinson et al . ).…”
Section: Reflections On the Use Of Focus Groups And Humour To Capturesupporting
confidence: 91%
“…The excerpt about laundering bed sheets shows that in these focus group settings encouraging curiosity about others, openness and humour enabled the participants to explore what they found interesting or incongruent about each other's practices, and challenge held social norms and meanings. Focus groups or similar informal multi‐person conversations in which humour and laughter feature enact a new type of data (Robinson ). The focus group is therefore a currently underused but potentially fruitful method to research mundane everyday practices because it allows new data to emerge, particularly about social meanings and conventions, the social organisation of everyday practices and connections across bundles of practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of laughter is also interesting. Laughter has been identified as enabling people to talk about sensitive topics (Robinson 2009) and an indicator of 'troubles-talk' (Jefferson 1984) -it suggests rhetorical discomfort in acknowledging an addiction. S126 describes cigarettes as yielding power over her, and suggests that addiction 'causes' her to go to extreme measures to access cigarettes.…”
Section: Accepting a Nicotine Addictionmentioning
confidence: 99%
“…Philamena orients to her smoking as problematic in a slightly different way to Sarah and Jessica, by using humour and laughter. Humour has been identified as facilitating difficult discussions in focus groups with low-income smoking mothers (Robinson, 2009) and, within conversation analysis, a prevalent feature of people's 'troubles-talk' (Jefferson, 1984). Philamena quotes her doctor as a way of justifying her (reduced) smoking, which according to the doctor is 'not going to be a massive stress [for her unborn foetus]'.…”
Section: Smoking In Pregnancy As Moral Troublementioning
confidence: 99%